Poly(C)-binding protein interacts with the hepatitis C virus 5′ untranslated region - Spångberg, Karin; Schwartz, Stefan (Journal of General Virology, 1999)
We have investigated whether poly(C)-binding protein (PCBP)-1 and PCBP-2 interact with the hepatitis C virus (HCV) 5′ untranslated region. Our results demonstrate that glutathione S-transferase (GST)-PCBP-1 and GST-PCBP-2 fusion proteins bind specifically to the HCV 5′ untranslated region. An antiserum raised against PCBP-2 induced a supershift after incubation with RNA-protein complexes formed between proteins in a HeLa cell cytoplasmic extract and the HCV 5′ untranslated region, indicating that this interaction occurs intracellularly. The complete internal ribosome entry site was necessary for efficient binding, suggesting that maintenance of the secondary structure was necessary for recognition of the binding site by the PCBPs.